Spatially explicit trends in nitrogen use efficiency and partial profits in Tanzania, 2008-2020 - Mkondiwa, Maxwel; Chamberlin, Jordan (International Maize and Wheat Improvement Center, 2024)
Amidst concerns of global agricultural productivity growth slowdown, there is an emerging consensus that crop productivity growth in some African countries has either been stagnant or slow in the past decade. This slowdown is attributed to degrading soil health and volatile weather patterns resulting in low partial productivity especially of nitrogen—hereafter nitrogen use efficiency (NUE) and falling profits. We contribute to this literature by using plot level nationally representative panel data (2008-2020) for Tanzania to examine if indeed NUEs and profits have been on a downward spiral. We combine a causal random forest model for heterogeneous treatment effects and a regional market economic surplus model to explore the economic implications of the NUE trends. We find that NUEs differ not only across years, but also spatially. Additionally, the whole crop response curve differs across seasons and regions which poses enormous complexity when understanding NUEs using observational data implying that complex processes operate in low input farms that make it difficult to pin down the major challenges causing any slowdowns or increases in NUEs. We do not find any evidence of falling NUEs in Tanzania. Conversely, NUEs have increased as compared to 2008 (9 kg maize per kg of N) by about 10% in 2010, 18% in 2012, 18% in 2014 and 14% in 2020. Nonetheless, the profits and economic surpluses from nitrogen use are too low to incentivize farmers to use nitrogen fertilizers at the prevailing input and maize output price ratios. To address food insecurity concerns while incentivizing farmers to apply modest amounts of nitrogen fertilizer, this paper argues for increasing NUEs through proper crop management decisions and minimizing the fertilizer-maize grain price ratios.